Recovery of voluntary and evoked muscle performance following intermittent-sprint exercise in the heat - Duffield, R.; King, M.; Skein, M. (International Journal of Sports Physiology and Performance, 2009)
Purpose: This study investigated the effects of hot conditions on the acute recovery of voluntary and evoked muscle performance and physiological responses following intermittent exercise. Methods: Seven youth male and six female team-sport athletes performed two sessions separated by 7 d, involving a 30-min exercise protocol and 60-min passive recovery in either 22°C or 33°C and 40% relative humidity. The exercise protocol involved a 20-s maximal sprint every 5 min, separated by constant-intensity exercise at 100 W on a cycle ergometer. Maximal voluntary contraction (MVC) and a resting evoked twitch (Pf) of the right knee extensors were assessed before and immediately following exercise and again 15, 30, and 60 min postexercise, and capillary blood was obtained at the same time points to measure lactate, pH, and HCO3. During and following exercise, core temperature, heart rate and rating of perceived exertion (RPE) were also measured. Results: No differences (P = 0.73 to 0.95) in peak power during repeated sprints were present between conditions. Postexercise MVC was reduced (P < .05) in both conditions and a moderate effect size (d = 0.60) indicated a slower percentage MVC recovered by 60 min in the heat (83 ± 10 vs 74 ± 11% recovered). Both heart rate and core temperature were significantly higher (P < .05) during recovery in the heat. Capillary blood values did not differ between conditions at any time point, whereas sessional RPE was higher 60 min postexercise in the heat. Conclusions: The current data suggests that passive recovery in warm temperatures not only delays cardiovascular and thermal recovery, but may also slow the recovery of MVC and RPE.